Do speed cameras reduce speeding in urban areas? - Daniele Falci de Oliveira; Amélia Augusta de Lima Friche; Dário Alves da Silva Costa; Sueli Aparecida Mingoti; Waleska Teixeira Caiaffa (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2015)
Abstract This observational study aimed to estimate the prevalence of speeding on urban roadways and to analyze associated factors. The sample consisted of 8,565 vehicles circulating in areas with and without fixed speed cameras in operation. We found that 40% of vehicles 200 meters after the fixed cameras and 33.6% of vehicles observed on roadways without speed cameras were moving over the speed limit (p < 0.001). Motorcycles showed the highest recorded speed (126km/h). Most drivers were men (87.6%), 3.3% of all drivers were using their cell phones, and 74.6% of drivers (not counting motorcyclists) were wearing their seatbelts. On roadway stretches without fixed speed cameras, more women drivers were talking on their cell phones and wearing seatbelts when compared to men (p < 0.05 for both comparisons), independently of speed limits. The results suggest that compliance with speed limits requires more than structural interventions.